(untitled) (Research, Society and Development, 2021)
Objective: To evaluate the role of the school in oral health education of schoolchildren, covering the entire pedagogical team. Methods: the exploratory research took place through the application of questionnaires directed to the school’s educational team, in order to obtain the data in the interview format. The data was transported to Google Forms, followed by the creation of a spreadsheet and graphs provided by the software itself. Results: A total of 11 volunteers belonging to the school team were evaluated. The percentages found were high with regard to the theme: the school’s role as a partner of parents in oral hygiene instruction added to the optimistic results regarding the previous knowledge and self-care of the respondents. Conclusion: it was possible to realize that the school plays an important role in oral health education and that it acts as an important public policy tool for the prevention and control of caries and periodontal diseases, becoming indispensable, especially in the polarization group.